St. Mary's County Civil War Records a.k.a St. Mary's Men Who Served in the War Between the States - Beitzell, Edwin Warfield
Bound photocopy of Edwin Beitzel's unpublished, handwritten manuscript with the names of St. Mary's County men who served in the civil war. Lists are divided into six folders (selectable using bookmarks in the document): 1) Unionists, 2) Notes, 3) Confederacy, 4) Federal Draft Enrollment Books, 5) US Service Black, and 6) US Service White. Every entry is meticulously documented with references. This is the only known comprehensive list of St. Mary's County Civil War soldiers. The original handwritten manuscript is in the Archives.